A Perbandingan Daya Listrik Panel Surya Menggunakan MPPT P&O terhadap MPPT Logika Fuzzy - Indra Budi Hermawan; Annisa Harumwidiah (Universitas Darul Ulum, 2021)
The electricity generated by solar panels up and down is influenced by weather, panel angle to the sun, ambient temperature and so on. When there is a change in the radiation level, the electric current generated by the solar panel also changes, causing a non-conformity with the load characteristics. This result in the electrical power generated by the solar panel is not optimal. Maximum Power Point Tracker (MPPT) can solve this problem by tracking the changes of electric current generated by the solar panel. The tracking apparatus is then connected to a control device and a DC / DC converter that converts and adjusts the optimum voltage and current according to the load. This study compares the amount of electricity generated by solar panels by using the Perturb and Observe (P & O) MPPT algorithm against the Fuzzy Logic Controller MPPT (FL). This research will be conducted on 100 Watt Solar Power Plant (PLTS) module by using Microcontroller ATMega318 as the controller. The results obtained are MPPT Fuzzy Logic Controller (FL) produce 5.61% more power than the Perturb and Observe (P&O) MPPT algorithm.